MANHAJ IJTIHAD AND CHARACTERS OF NONFORMAL EDUCATION STUDENTS IN DEALING WITH INDUSTRIAL ERA CHALLENGES 4.0 - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
This article examines the classic literature on Manhaj Ijtihad and concepts that focus on reading the predictions of the character of non-formal education students at the University of Muhammadiyah Enrekang in facing the challenges of the Industrial 4.0 era. The theory studied is the high urgency about the industrial era 4.0 in the area of ​​contemporary jurisprudence ijtihad, because the nature of contemporary fiqh itself tends to rely on the benefit of the world and the hereafter. Predictions of benefit that can be used as legal support, although the consequences will leave the original law contained in the text. Besides mashlahah, there are several factors that require the concept to be studied, namely Ma'lât Al-Af'âl which is recognized in the realm of ijtihad, such as sad Al-Zarîah, Al-Dharûrah, raf`u Al-Haraj and ta`lil Al-Ahkâm. As a temporary study material that is needed in solving contemporary problems in the character of Non-formal Education students of the University of Muhammadiyah Enrekang in implementing Manhaj Ijtihad as a benchmark, namely maqâshid syarî`ah which leads to the benefit of the world and the hereafter in facing the challenges of the Industrial 4.0 era.